2004
DOI: 10.1152/japplphysiol.00239.2004
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic control of the cardiovascular system during acclimatization to high altitude: effects of sildenafil

Abstract: Both acute hypoxia and sildenafil may influence autonomic control through transient cardiovascular effects. In a double-blind study, we investigated whether sildenalfil (Sil) could interfere with cardiovascular effects of hypoxia. Twelve healthy men [placebo (Pla) n = 6; Sil, n = 6] were exposed to an altitude of 4,350 m during 6 days. Treatment was continuously administered from 6 to 8 h after arrival at altitude (3 x 40 mg/day). The autonomic control on the heart was assessed by heart rate variability (HRV) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 32 publications
3
49
3
Order By: Relevance
“…The increase in the ratio is believed to imply that the sympathetic system is dominant compared to the parasympathetic. Similar results were obtained by Cornolo et al [ 91 ] who reported that exposure to an altitude of 4,350 m for 1-2 days reduced power in the highfrequency band but increased low-frequency power, thereby increasing the low to high frequency ratio. From this they concluded that acute exposure to hypoxia is associated with decreased parasympathetic and increased sympathetic tone.…”
Section: Heart Rate Variabilitysupporting
confidence: 89%
“…The increase in the ratio is believed to imply that the sympathetic system is dominant compared to the parasympathetic. Similar results were obtained by Cornolo et al [ 91 ] who reported that exposure to an altitude of 4,350 m for 1-2 days reduced power in the highfrequency band but increased low-frequency power, thereby increasing the low to high frequency ratio. From this they concluded that acute exposure to hypoxia is associated with decreased parasympathetic and increased sympathetic tone.…”
Section: Heart Rate Variabilitysupporting
confidence: 89%
“…Analyses showed an increase in the LH/HF ratio during acclimatization (Sevre et al, 2001). Since HF power is assumed to be a marker of parasympathetic activity and LF power to be a combination of both parasympathetic and sympathetic tonic activity, it has been concluded that the sympathetic tone is less reduced than the parasympathetic control of HR upon high-altitude exposure (Sevre et al, 2001;Cornolo et al, 2004).…”
Section: Cardiovascular Responsementioning
confidence: 99%
“…12 Preliminary studies measuring HRV during acute hypobaric hypoxia exposure reported a reduction in HRV by means of a decrease in total spectral power. 13,14 These studies demonstrated a change in the sympathetic---parasympathetic balance, in that the relative sympathetic tone increases along with a decrease in parasympathetic tone. A relationship between changes in VO 2 max and HRV alterations during acute hypobaric hypoxia has also been observed, with a decrease in the power of the high (HF) and low frequency (LF) bands and an increase in the LF/HF ratio.…”
Section: Introductionmentioning
confidence: 99%